A scalable dissemination service for the ISAM architecture - Moraes, M.; Silva, L. da; S. Filho, A.; Geyer, C. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
The ISAM architecture presents a platform to the development and to the execution of pervasive applications. DIMI (Disseminador Multicast de Informacoes - information multicast disseminator) is an information dissemination service designed for the ISAM architecture. DIMI seeks mainly to obtain scalability, avoiding bottlenecks formation while accepting new consumers on a channel. Besides the search for scalability, this service outfits other necessary characteristics of the computational environment proposed by the ISAM architecture, as planned disconnection support and user mobility support.